Mesh erosion into the rectum after laparoscopic posterior rectopexy: A case report. (June 2022) - Yamanaka, Shun; Enomoto, Tsuyoshi; Moue, Shoko; Owada, Yohei; Ohara, Yusuke; Oda, Tatsuya
Abstract: Introduction: Rectal prolapse typically presents in elderly women with protruding full-thickness rectum from the anus. Rectopexy using mesh is known to be a highly curative treatment for rectal prolapse, however, this procedure carries the risk of severe complication as mesh erosion. Presentation of case: A 78-year-old woman who had undergone laparoscopic posterior rectopexy 4 years earlier visited the outpatient clinic with a complaint of bloody stool. A colonoscopy and computed tomography revealed that part of the mesh had migrated into the rectal lumen at 8 cm from the anal verge. Based on the above findings, a diagnosis of mesh erosion into the rectum was made. Complete removal of the mesh and tacker with rectal resection was performed. Before rectopexy, the patient had severe fecal incontinence, and her anal sphincter function was decreased, therefore, Permanent colostomy was indicated instead of anastomosis. In the resected specimen, the mesh was folded and placed in the mesenteric fat of the posterior wall of the rectum, with the corner of the edge of the mesh protruding into the inside lumen. Discussion: Mesh erosion typically occurs when using mesh made of synthetic mesh and non-absorbable threads; it might induce chronic irritation and friction due to mesh shrinkage. Conclusion: To prevent mesh erosion, it is important to pay attention to the mesh materials used and ensure secure fixation. Highlights: Mesh erosion into rectum after Laparoscopic posterior rectopexy was reported. Complete removal of the mesh and tacker with rectal resection was needed. Colostomy was made because of existence of severe fecal incontinence, preoperatively. Paying attention to the Shrinkage and secure fixation of synthetic mesh.